The Role of Student Led Organizations in Developing Leadership and Soft Skills in Higher Education - Dewanti, Lucky; Astuty, Henny Sri; R, Rinovian; Soelistiyono, Anitiyo; Berliani, Tety (Asian Journal of Applied Education (AJAE), 2025)
This study examines the role of student organization participation in developing leadership skills and soft skills in higher education. Recognizing that universities must foster not only academic achievement but also competencies relevant to professional needs, the research employs a quantitative survey method using a Likert scale questionnaire distributed to 120 active students from three universities in Bogor, Tuban, and Jakarta. Data were analyzed using multiple linear regression to assess the influence of organizational participation levels. The results indicate that involvement in student organizations has a positive and significant impact on leadership and soft skills, particularly in communication, teamwork, and decision-making. These findings highlight the vital role of student organizations as complementary non-formal learning spaces that provide contextual and practical experiences. The study contributes both theoretically to higher education research and practically by offering insights for universities in designing strategies to enhance leadership and soft skills through student organization empowerment.